Eco-critical Praxis: Unravelling and Recuperating Eco-trauma in Leslie Marmon Silko’s Gardens in the Dunes - Shokofeh Zorriyeh Habib; Leila Baradaran Jamili (Critical Literary Studies)
This article unravels the concept of eco-trauma in American Indians’ lifestyle in Gardens in the Dunes (2000), a novel portraying eco-concerns of Leslie Marmon Silko (1948). Silko’s novel is preoccupied with ecological concerns of American Indians who depend on nature to continue their existence. Being detached from their ancestral lands, Indians encountered several psychological problems due to their indispensable loyalty to nature. This article focuses on the significance of environment and ‘place’ according to Lawrence Buell (1939), and traces ‘place’ as the center of feeling for a person. Cheryll Glotfelty’s connection between nature and culture, and Cathy Caruth’s perspective on trauma have been utilized to explain Indians’ psychological problems due to loss of ancestral lands. Eco-traumatic approach illustrates the interrelation of Native American’s identity and culture with their living place. Indeed, Indians return to their land to eliminate their environmental concerns. Their ceaseless effort to reverse eco-trauma by adhering to their ancestral ritual is also examined in this article. Silko re-emphasizes and stipulates that the notion of nature can consolidate Indians’ identity; hence, loyalty to natural environment ensures how Native Americans’ loss of land and nature opens up the experience of eco-loss or eco-trauma and diminishes Native Americans’ culture.